2022
DOI: 10.1111/ppa.13668
|View full text |Cite
|
Sign up to set email alerts
|

Fusarium isolates from Belgium causing wilt in lettuce show genetic and pathogenic diversity

Abstract: Fusarium oxysporum f. sp. lactucae race 4 causes vascular necrosis and wilting of lettuce. First observed in Belgium in 2015, the lack of disease resistance in commercial cultivars allowed this pathogen to spread to nearly the entire Belgian production area within 4 years. Different levels of disease development were observed in different commercial greenhouses. To help explain this variation, we collected 78 Fusarium isolates and characterized them both physiologically and genetically. Molecular race identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…Firstly, phylogenetic analysis of both core and accessory genomes indicated that Fola1 and Fola4 were in sister clades derived from a common ancestor. This is also supported by a previous report where Fola1 and Fola4 isolates were consistently shown to be in distinct vegetative compatibility groups (Pintore et al, 2017) and by GBS based phylogenetic analysis (Claerbout et al, 2023). Secondly, the mimp -associated effector profile for Fola1 and Fola4 also separates them into separate clusters.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Firstly, phylogenetic analysis of both core and accessory genomes indicated that Fola1 and Fola4 were in sister clades derived from a common ancestor. This is also supported by a previous report where Fola1 and Fola4 isolates were consistently shown to be in distinct vegetative compatibility groups (Pintore et al, 2017) and by GBS based phylogenetic analysis (Claerbout et al, 2023). Secondly, the mimp -associated effector profile for Fola1 and Fola4 also separates them into separate clusters.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, Fola1 also seems to be spreading into Northern Europe with new reports on protected lettuce in both Norway (Herrero et al, 2021) and Northern Ireland (van Amsterdam et al, 2023). This suggests that in the near-future both Fola1 and Fola4 may co-exist in many locations affecting both protected and field-grown lettuce, as is currently the case in some European countries such as Italy (Gilardi et al, 2017b), Belgium (Claerbout et al, 2023) and Spain (Guerrero et al, 2020; Gálvez et al, 2023). Fola4 and Fola1 are very closely related based on phylogenetic analyses of DNA sequences of standard loci such as the translation elongation factor 1α, while Fola2 and Fola3 are in separate distinct clades (Gilardi et al, 2017a; Claerbout et al, 2023).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The pathogen, first reported in Japan (Matuo and Motohashi, 1967) is divided into four races, of which race 1 is the most widespread. In Europe, race 1 was first discovered in 2001 in Italy (Garibaldi et al, 2002), then in Portugal (Pasquali et al, 2007), France (Gilardi et al, 2017b), Spain (Guerrero et al, 2020), Norway (Herrero et al, 2021), Belgium (Claerbout et al, 2023), Greece (Tziros and Karaoglanidis, 2023) and Ireland (van Amsterdam et al, 2023). Since 2015, a new race (race 4) has emerged as a serious threat to lettuce production in several European countries.…”
Section: Introductionmentioning
confidence: 99%
“…The persistence of Fol in soil poses significant management challenges as restrictions on the use of soil fumigants make it difficult to reduce the Fol inoculum in soil . The pathogen can spread via infested soil on equipment as well as via infected seed (Garibaldi et al, 2004a;Claerbout et al, 2023). The use of resistant lettuce cultivars can be an effective control method against the disease, but currently no commercially viable resistant lettuce varieties are available.…”
Section: Introductionmentioning
confidence: 99%